Answer:
y=30x^2+36x+48 OR f(x)=30x^2+36x+48
This is an exponential function/exponential graph. Hope I helped!
Step-by-step explanation:
Given: y=2(3x+6)(5x-4)
Use the distributive property!: y=(6x+12)(5x-4)
Use the distributive property!: y=(5x(6x+12)-4(6x+12))
Use the distributive property!: y=(30x^2+60x)-(24x+48)
Remove parenthesis: y=30x^2+60x-24x+48y=30x^2+36x+48 OR f(x)=30x^2+36x+48
This is an exponential function/exponential graph. Hope I helped!
Answer:
$15
Step-by-step explanation:
Let's start by figuring out how much 1 cup of oil costs.
12 cups of oil is 36$
Let's set up a proportion.
12/36=1/x
Cross Multiply
12x=36
Divide both sides by 12.
x=3
1 cup of oil is $3.
Dinesh makes 5 batches of hummus, and each batch requires 1 cup of oil.
5*1=5
This means he needs 5 cups of oil.
5*3=15
He used $15 worth of oil in the 5 batches of his recipe.
However, since it is impossible to buy 5/12 bottles of oil, he would have needed to spend $36.
Answer:
x = 5/2 or x = 2.5
Step-by-step explanation:
To solve for x, we will have to get the equation 2x + 15 = 20 into the form x = _. That will be our answer.
2x + 15 = 20
Subtract 15 from both sides to get rid of the +15 on the left side.
2x = 20 - 15
Simplify.
2x = 5
Divide both sides by 2 to get rid of the coefficient of 2 on the left side.\
x = 5/2 = 2.5
x = 5/2 or x = 2.5
I hope you find my answer helpful. :)
Answer:
-30(-8)
Step-by-step explanation:
A negative times a negative always equals a positive.
Answer:
b = 1
Step-by-step explanation:
Given the equation is:
- 5b + 2b - (-b) + 7 = 5
We separate the terms of b and the constants. To do that we subtract 7 from both the sides. We get:
- 5b + 2b - (-b) + 7 - 7 = 5 - 7
⇒ - 5b + 2b - (-b) = - 2
Now, simplifying the terms with 'b'.
⇒ -5b + 2b + b = - 2
⇒ (-5 + 2 + 1)b = - 2
⇒ -2b = -2
Dividing both the sides by -2, we get:
b = 1 which is the required answer.